Reproductive Biology of the Green Tiger Prawn (Penaeus semisulcatus) in Coastal Waters of Bushehr, Persian Gulf - Niamaimandi, Nassir; Arshad, Aziz; Daud, Siti Khalijah; Saad, Che Roos; Kiabi, Bahram (Oxford University Press, 2008)
The reproductive cycle of the green tiger prawn (Penaeus semisulcatus) was investigated in the coastal waters of Bushehr, Iran, Persian Gulf, from January 2003 to March 2004, with the aim of determining spawning seasons, durations, and locations in those waters. Bushehr waters are one of the main fishing grounds for P. semisulcatus in the Persian Gulf. Spawning peaks between December and March, but there is also some spawning in October. The minimum size at maturity was 24 mm carapace length (CL), and 50% were mature at 40 mm CL. The proportion of females that mated increased sharply above this size (40 mm), with 90% of females sexually mature at 54 mm CL. Spawning took place in a limited part of the study area, mostly offshore. Overexploiting the spawning stock could result in reduced reproductive output, limiting fishery production.